Investigation on the difference expression of type IV collagen α1(IV)- α6(IV) chain mrna in normal fibroblast and in skin cell malignant melanoma - Mohammad, Mardhiah; Mat Yusof, Afzan; Kaja Mohideen, Syahirah; Syed Bahrom, Sharifah Norbaizura; Roshdi, Ridhwan; Parman, Adibah (Universiti Teknologi Malaysia, 2015)
Collagen IV is the major basement membrane protein that influences adhesion, proliferation, and migration of cells. The collagen composed of a network chains α1 to α6. The characterization of this collagen IV will correlates the relationship of collagen gene expression and cancer. This is important in order to provide more detailed understanding of the expression of collagen in tumor cells. . The aim of this study is to determine the α1 to α6 (IV) mRNA expression in the cell lines obtained from skin and melanoma cell. To investigate the mRNA expression, the RNA was extracted from the fibroblast and melanoma (A375) cell lines. The RNA was subjected to reverse transcription and then synthesized. The mRNA expression levels were measured using real time PCR with related to internal control, GAPDH. The study identified that α1, α2, α4, α5 and α6 of the α1-α6 (IV) were expressed in skin fibroblast. This corresponds to the α1α1α2 and a5α5α6 networks. However, in melanoma cell lines the collagen IV α2, α4, α5 and α6 mRNA was observed in low level compared to α1 and this suggested that the tumor has affected the expression of collagen and basement membrane of the cell.